Analisis Perputaran Piutang Pada Perusahaan Besi dan Stainless PT. XYZ - Amilia Fajrin; Anita Handayani (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
Credit sales can cause arrears in payment of goods made by some customers who buy iron and stainless at PT. XYZ is like a contractor company, both small and large scale. This study aims to analyze the receivables turnover at PT. XYZ using a qualitative descriptive method. The results showed that the total receivables turnover for eleven months (8.42/11) was 0.76 times. Accounts receivable turnover that occurs from January 2021 to November 2021 is 0.76, so it can prove that the turnover made by PT. XYZ is quite good. In the period of collection of receivables which is also influenced by the level of receivables turnover of PT. XYZ also fluctuated, where the longest and most detrimental period was in May with 180 days. For this reason, it is expected that PT. XYZ can further optimize and maintain the performance of each division related to the existing credit sales system, especially the collection division, so that there is no significant decline in receivable turnover results.